Weight loss is not mandatory for exercise-induced effects on health indices in females with metabolic syndrome - Farinha, Juliano; dos Santos, Daniela; Bresciani, Guilherme; Bard, Laisa; de Mello, Flaviane; Stefanello, Sílvio; Courtes, Aline; Soares, Félix (Biology of Sport, 2015)
The aim of this study was to investigate the impact of moderate aerobic training on functional, anthropometric, biochemical, and health-related quality of life (HRQOL) parameters on women with metabolic syndrome (MS). Fifteen untrained women with MS performed moderate aerobic training for 15 weeks, without modifications of dietary behaviours. Functional, anthropometric, biochemical, control diet record and HRQOL parameters were assessed before and after the training. Despite body weight maintenance, the patients presented decreases in waist circumference (P=0.001), number of MS components (P=0.014), total cholesterol (P=0.049), HDL cholesterol (P=0.004), LDL cholesterol (P=0.027), myeloperoxidase activity (P=0.002) and thiobarbituric acid-reactive substances levels (P=0.006). There were no differences in total energy, carbohydrate, protein and lipid intake pre- and post-training. Furthermore, improvements in the HRQOL subscales of physical functioning (P=0.03), role-physical (P=0.039), bodily pain (P=0.048), general health (P=0.046) and social functioning scoring (P=0.011) were reported. Despite the absence of weight loss, aerobic training induced beneficial effects on functional, anthropometric, biochemical and HRQOL parameters in women with MS.